PENGARUH KINERJA KEUANGAN TERHADAP REAKSI PASAR DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING - Fajri, Febiyanti Nurul; asyik, nur fadjrih (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
This Research aimed to examine the effect of financial performance on the market reaction with Corporate Social Responsibility as the moderating variable. In This research used the quantitative in the property and real estate sector companies that listed on The Indonesia Stock Exchange and companies sample it was selected by the purposive sampling, that is the sample collection technique with special consideration determined by 12 companies sampled the property and real estate sector in the observation year of start 2015 until year 2020. Furthermore, the data analysis method used multiple regressions. The data in this research were processed by software SPSS 25 version. The research result showed that financial performance had a positive significant effect on the firm value and Corporate Social Responsibility was moderated by the financial performance effect on the firm value; it meant the higher the Corporate Social Responsibility value in companies would affect the financial performance on the firm value.